Determining Trace Elements and Heavy Metals in Chinese Herbal Medicine Panax notoginseng from Tibet - Chen, Xiaofei; Rui, Yukui; Yu, Ying (Asian Journal of Chemistry, 2011)
Wild Panax notoginseng from Tibet were determined the contents of trace elements and heavy metals by ICP-MS. Data proved that Panax notoginseng from Tibet contains more Fe, Mn, Zn and Se than Panax notoginseng from Guangxi province of China and more Fe, Mn, Zn, Se and Mo than Panax notoginseng from Yunnan proveince of China, but Panax notoginseng from Tibet contains less Cu than that from Guangxi proveince of China and less Ca and Se than that from Yunnan province of China, which proved that wild Panax notoginseng from Tibet of China has higher quality in terms of trace elements. Compared with Panax notoginseng from Guangxi province, Panax notoginseng from Tibet contains less Pb and more As and more Pb than Panax notoginseng from Yunnan province, so we should control and detect the heavy metals content when control the quality of Chinese traditional medicine.